A Case of Extrauterine Endometrial Stromal Sarcoma in the Colon Diagnosed Three Decades after Hysterectomy for Benign Disease. (24th April 2013) - Ayuso, Andres; Fadare, Oluwole; Khabele, Dineo
Abstract : Extrauterine endometrial stromal sarcoma (ESS) is rare and typified by delayed recurrence of primary ESS. Here, we report an unusual case of colonic ESS in a woman with a remote history of hysterectomy. An 80-year-old woman, with a history of hysterectomy and bilateral salpingo-oophorectomy for abnormal bleeding and endometriosis 37 years prior to presentation, was diagnosed with ESS in the colon. She was treated with laparoscopic low anterior resection, followed by megestrol acetate, and has been in remission for more than 4 years. This case highlights the rarity of extra-uterine ESS in the colon, especially in the absence of a known history of primary uterine ESS. The patient's history of endometriosis may have been a predisposing risk factor. ESS in the colon may be treated successfully with surgical resection and progestin therapy. Indefinite surveillance is recommended to monitor for late recurrences.